Ventricular Dyssynchrony and Function Improve following Catheter Ablation of Nonseptal Accessory Pathways in Children. (18th June 2013) - Abadir, Sylvia; Fournier, Anne; Dubuc, Marc; Sarquella-Brugada, Georgia; Garceau, Patrick; Khairy, Paul
Abstract : Introduction . Paradoxical or hypokinetic interventricular septal motion has been described in patients with septal or paraseptal accessory pathways. Data regarding nonseptal pathways is limited. Methods and Results . We quantified left ventricular dyssynchrony and function in 16 consecutive children, 14.2 ± 3.7 years, weighing 53  ±  17  kg, prior to and following catheter ablation of bidirectional septal (N = 6 ) and nonseptal (N = 10 ) accessory pathways. Following ablation, the left ventricular ejection fraction increased by 4.9 ± 2.1 % (P = 0.038 ) from a baseline value of 57.0 % ± 7.8 % . By tissue Doppler imaging, the interval between QRS onset and peak systolic velocity (Ts) decreased from a median of 33.0 ms to 18.0 ms (P = 0.013 ). The left ventricular ejection fraction increased to a greater extent following catheter ablation of nonseptal (5.9 % ± 2.6 %, P = 0.023 ) versus septal (2.5 % ± 4.1 %, P = 0.461 ) pathways. The four patients with an ejection fraction <50%, two of whom had left lateral pathways, improved to >50% after ablation. Similarly, the improvement in dyssynchrony was more marked in patients with nonseptal versus septal pathways (difference between septal and lateral wall motion delay before and after ablation 20.6 ± 7.1  ms (P = 0.015 ) versus 1.4 ± 11.4  ms (P = 0.655 )). Conclusion . Left ventricular systolic function and dyssynchrony improve after ablation of antegrade-conducting accessory pathways in children, with more pronounced changes noted for nonseptal pathways.